“Estudio del funcionamiento de la transmisión automática 4L60-E del vehículo Chevrolet Tahoe y su aplicación en el proceso de enseñanza aprendizaje de los estudiantes del tercer año de bachillerato, especialidad Electromecánica Automotriz de la unidad educativa “Carlos Cisneros”, período 2016”. - Guallo Choca, Armando Moisés (2016)
The present research was about Study of Automatic Transmission Function 4L60-E of the Chevrolet Tahoe vehicle and its application in the teaching-learning process for the students from Electromechanics Automotive of the third year of bachelor at the “Carlos Cisneros” during the academic year 2015. It was developed with the objective to design and development an educational blog with the content of the automatic transmission 4L60-E, for application in the process of teaching and learning as a tool for pedagogical support, giving openness of the use of information technology and communication (ICT), using the VLE ( Virtual Environment Teaching and Learning) methodology, innovating educational technology since it is essential and fundamental allowing generate learning and strengthen their skills. In the research was applied bibliographical and descriptive method in the field, level of the diagnostic investigation, the technique that was used for the collection of information was through a survey applied to the students, taking into account the appropriate methodology for the student catching their knowledge and developing their skills, has been concluded according to the results obtained from the techniques applied, before the application of the educational blog there were learning problems and lacked knowledge of the subject raised, through implementation was improved the learning performance of students showing greater interest in learning and actively participating, so that they better assimilated the content exposed in the subject, making new forms of student-teacher communication.